1996
DOI: 10.1017/s0022215100134292
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in an intralabyrinthine acoustic neuroma patient after resection of an intracanalicular tumour

Abstract: This case study describes a therapeutic strategy using a cochlear implant for a bilateral acoustic neuroma deafened patient. The cochlear nerve had previously been sacrificed on one side during tumour removal, but on the remaining side a functioning cochlear nerve was assessed by electric promontory stimulation in spite of a neuroma extending into the vestibular labyrinth. The patient was successfully stimulated with a Nucleus 22- channel implant after removal of the intracanalicular portion of the neuroma via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Since this initial study, the cases of 32 patients with NF2 who have received cochlear implants have been reported in the literature. 1,2,7,12,15,16,2023,29,30,32,34 Our study demonstrates open-set speech recognition in 4 of 7 patients with NF2 who had cochlear implants. We acknowledge that our results represent a retrospective assessment of patients who were available for follow-up at our institution.…”
Section: Discussionmentioning
confidence: 54%
“…Since this initial study, the cases of 32 patients with NF2 who have received cochlear implants have been reported in the literature. 1,2,7,12,15,16,2023,29,30,32,34 Our study demonstrates open-set speech recognition in 4 of 7 patients with NF2 who had cochlear implants. We acknowledge that our results represent a retrospective assessment of patients who were available for follow-up at our institution.…”
Section: Discussionmentioning
confidence: 54%
“…Patients with NF-2 with profound hearing loss may be candidates for brainstem implants if the anatomical integrity of the cochlear nerve is not maintained. However, in cases of vestibular schwannoma resection in which the cochlear nerve has been spared, a cochlear implant in the same ear has been used to obtain hearing (Tono et al, 1996). Arriaga and Marks (1995) described a case of successful cochlear implantation simulta-neous with vestibular schwannoma resection in a patient with co-existing otosclerosis in the ear contralateral to the acoustic neuroma.…”
Section: Acoustic Neuroma and Neurofibromatosis Type 2 (Nf2)mentioning
confidence: 99%
“…Several studies suggest a very good hearing rehabilitation of acoustic neuroma patients after CI 9,17,18 . However, nearly all studies are limited due to small patient numbers 19,20 -reporting case files or groups of up to 3 patients. Another shortcoming of the studies reported in the literature is the lack of information on improvements regarding impairments associated with an acoustic neuroma, for example tinnitus and vertigo.…”
Section: Introductionmentioning
confidence: 99%